Cartilage Endplate Stem Cells Transdifferentiate Into Nucleus Pulposus Cells via Autocrine Exosomes - Luo, Liwen; Gong, Junfeng; Zhang, Hongyu; Qin, Jinghao; Li, Changqing; Zhang, Junfeng; Tang, Yu; Zhang, Yang; Chen, Jian; Zhou, Yue; Tian, Zhiqiang; Liu, Yao; et al. (Frontiers in Cell and Developmental Biology, 2021)
Stem cells derived from cartilage endplate (CEP) cells (CESCs) repair intervertebral disc (IVD) injury; however, the mechanism remains unclear. Here, we evaluated whether CESCs could transdifferentiate into nucleus pulposus cells (NPCs) via autocrine exosomes and subsequently inhibit IVD degeneration (IVDD). Exosomes derived from CESCs (CESC-Exos) were extracted and identified by ultra-high-speed centrifugation and transmission electron microscopy (TEM). The effects of exosomes on the invasion, migration, and differentiation of CESCs were assessed. The exosome-activating hypoxia-inducible factor (HIF)-1α/Wnt pathway was investigated using lenti-HIF-1α and Wnt agonists/inhibitors in cells and gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis in normal and degenerated human CEP tissue. The effects of GATA binding protein 4 (GATA4) on transforming growth factor (TGF)-β expression and on the invasion, migration, and transdifferentiation of CESCs were investigated using lenti-GATA4, TGF-β agonists, and inhibitors. Additionally, IVD repair was investigated by injecting CESCs overexpressing GATA4 into rats. The results indicated that CESC-Exos promoted the invasion, migration, and differentiation of CESCs by autocrine exosomes via the HIF-1α/Wnt pathway. Additionally, increased HIF-1α enhanced the activation of Wnt signaling and activated GATA4 expression. GATA4 effectively promoted TGF-β secretion and enhanced the invasion, migration, and transdifferentiation of CESCs into NPCs, resulting in promotion of rat IVD repair. CESCs were also converted into NPCs as endplate degeneration progressed in human samples. Overall, we found that CESC-Exos activated HIF-1α/Wnt signaling via autocrine mechanisms to increase the expression of GATA4 and TGF-β1, thereby promoting the migration of CESCs into the IVD and the transformation of CESCs into NPCs and inhibiting IVDD.